Comparison of hidden medical curriculum of Tabriz University of Medical Sciences and Tabriz Azad University of Medical Sciences from the students' perspectives - Amir Nahavandi Takab; Eskandar Fathi Azar; Zarrin Daneshvar Heris; Hossein Baghaei (Tabriz University of Medical Sciences, 2021)
Background: Considering components of the hidden curriculum in medicine in the higher education system is a useful adjunct to the formal curriculum since the learning and function of medical students are strongly affected by these components. The current study compares the hidden medical curriculum of Tabriz state and non-state Universities of Medical Sciences from the students' perspectives. Methods: In the current descriptive-comparative study, the statistical population included the total students of Tabriz state and non-state Universities of Medical Sciences. The statistical sample of the given study consisted of 400 students from senior and higher academic levels at the Tabriz state and non-state Universities of Medical Sciences based on Morgan's table. Two hundred students from each university were selected using stratified random sampling. The data collection tool was a researcher-created valid questionnaire. The validity and reliability of the given questionnaire in respect to its components were 0.94 and 0.76, respectively. In the analysis of data, an independent inferential T_test was utilized. Results: The results of the analysis found that from the students' perspectives, the mean scores of the hidden curriculum in medicine in the Tabriz state university of medical sciences ranked the following components higher than the Tabriz non-state university of Medical Sciences: (1) Education, including curriculum and goal-setting, clinical education and content, (2) Socialphysical environment, (3) Regulations and rules, including reward and punishment system, organizational structure, respect for rights and value system and (4) Relations, including moral behavior, approach, participation, and responsibility. However, in the fifth component of contexts and perspectives, including personal-environment/family context and professional financial perspectives, there was no significant difference between the hidden curriculum of Tabriz state and non-state Universities of Medical Sciences. Conclusion: The components of the hidden curriculum in medicine affect the learning richness and function of students and should be taken into consideration by universities of medical sciences, particularly non-state universities.